Plasmodium malariae and ovale genomes provide insights into malaria parasite evolution - Newbold, C; Rutledge, G; Böhme, U; Sanders, M; Reid, A; Cotton, J; Maiga-Ascofare, O; Djimdé, A; Apinjoh, T; Amenga-Etego, L; Manske, M; Barnwell, J; et al. (Nature Publishing Group, 2017)
Elucidating the evolutionary history and interrelatedness of human-infective Plasmodium species has been hampered by a lack of genetic information for three human-infective species: P. malariae and two P. ovale species (P. o. curtisi and P. o. wallikeri) . These species are prevalent across most malaria endemic regions 2,3 and are often undetectable by light microscopy, making their study in human populations difficult. The exact evolutionary relationship of these species to the other human-infective species has been contested. Using a new reference genome for P. malariae as well as a manually curated draft P. o. curtisi genome, we are now able to accurately place these species within the Plasmodium phylogeny. Sequencing of a chimpanzee-infective P. malariae relative reveals similar signatures of selection in the P. malariae lineage to another Plasmodium lineage where colonisation of both human and chimpanzee hosts has occurred. Molecular dating suggests that these host adaptations occurred over similar evolutionary timescales. In addition to the core genome that is conserved between species, differences in gene content can be linked to their specific biology. The genome suggests that P. malariae expresses a novel family of heterodimeric proteins on its surface that have structural similarities to a protein crucial for red blood cell invasion. The data presented here provide an essential foundation into understanding the evolution of the Plasmodium genus as a whole.